Mulch farming techniques for improving resource conservation, carbon sequestration and crop production in rainfed regions - A review - KAMBLE, TRUPTI; RAO, B. KRISHNA; SHARMA, RASHMI (Journal of Soil and Water Conservation, 2020)
Mulching is a technique which covers soil surface around the plants to create compatible condition for its growth. In this article a review on various types of mulching materials, their impact on water-use efficiency, soil properties, carbon-sequestration, runoff, soil and nutrient losses and crop production, have been systematically presented. The study recommended that organic mulches have significant impact on soil organic carbon build up and carbon sequestration. Plastic mulching is the best option for weed control and increases water use efficiency up to 90%.Straw mulches (@ 2-6 t ha-1) conserve moisture significantly and produce minimum runoff (up to 60%) and sediment losses (up to 75%). Gravel mulches play significant role in temperature control of soil. The knowledge gaps such as cost effective and readily available organic and inorganic mulching materials, their application rate, and runoff, soil and nutrients losses reduction potential in different agro ecological regions needs to be identified. Considering the benefits of mulching technique and change in crop productivity and resource conservation, this can be strongly recommended for widespread adoption of mulching in rainfed regions